2018
DOI: 10.1016/j.jctb.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic index determined by fractional chromatic index

Abstract: Given a graph G possibly with multiple edges but no loops, denote by ∆ the maximum degree, µ the multiplicity, χ ′ the chromatic index and χ ′ f the fractional chromatic index of G, respectively.where the upper bound is a classic result of Vizing. While deciding the exact value of χ ′ is a classic NP-complete problem, the computing of, where the maximality is taken over all induced subgraphs H of G. Gupta (1967), Goldberg (1973), Andersen (1977), andSeymour (1979) , which is commonly referred as Goldberg's con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…As the statement holds trivially when n = 1, we proceed to the induction step and assume that the statement has been established for n − 1; that is, (3)…”
Section: Algorithm 31mentioning
confidence: 99%
See 1 more Smart Citation
“…As the statement holds trivially when n = 1, we proceed to the induction step and assume that the statement has been established for n − 1; that is, (3)…”
Section: Algorithm 31mentioning
confidence: 99%
“…Nevertheless, this method suffers some theoretical limitation when applied to prove the conjecture; the reader is referred to Asplund and McDonald [2] for detailed information. Despite various attempts to extend the Tashkinov trees (see, for instance, [3,4,5,31,36]), the difficulty encountered by the method remains unresolved. Even worse, new problem emerges: it becomes very difficult to preserve the structure of an extended Tashkinov tree under Kempe changes (the most useful tool in edge-coloring theory).…”
Section: Introductionmentioning
confidence: 99%
“…Stiebitz, Scheide, Toft, and Favrholdt [37] have proven a fractional version of Conjecture 1. Much better approximations have been obtained for the case f = 1 of the chromatic index using the tool Tashkinov trees (see [9,10,33,38]). A proof of the case f = 1 has even recently been announced by Chen, Jing, and Zang [8], although it awaits verification.…”
Section: F-coloringsmentioning
confidence: 99%
“…In [6], and independently [26], it was shown that χ ′ (G) ≤ max{∆+ ∆ 2 , ⌈ρ(G)⌉}. A very recent breakthrough by Chen, Gao, Kim, Postle, and Shan [5] proves the best known upper bound of χ ′ (G) ≤ max{∆ + 3 ∆ 2 , ⌈ρ(G)⌉}. For a more thorough history of this important problem see [30].…”
Section: Introductionmentioning
confidence: 99%